Value of IL28B genotyping in patients with HCV‐related mixed cryoglobulinemia: results of a large, prospective study. Issue 4 (4th December 2012) - Piluso, A.; Giannini, C.; Fognani, E.; Gragnani, L.; Caini, P.; Monti, M.; Petrarca, A.; Ranieri, J.; Urraro, T.; Triboli, E.; Laffi, G.; Zignego, A. L.
Summary HCV‐related mixed cryoglobulinemia (MC) is characterized by clonal expansion of B cells producing a polyreactive natural antibody (rheumatoid factor) and interferon (IFN)‐based therapy is the first therapeutic option in mild‐moderate MC. Single nucleotide polymorphisms (SNPs) proximal to genes involved in the innate response (IL28B/IFN‐λ gene family) are strongly associated with spontaneous and IFN‐induced viral clearance in hepatitis C, but no data exist about their role in HCV‐positive MC. A large cohort of patients with HCV and MC was studied to evaluate the influence of IL28B genotype on the response to treatment and/or the evolution to MC of HCV infection. The rs12979860/rs8099917 IL28B polymorphisms were analysed in 481 consecutive HCV‐positive subjects (250 with MC and 231 without MC, as controls) using real‐time PCR and direct sequencing. Hundred and fifteen HCV patients with MC received standard anti‐HCV therapy, and the results were evaluated according to the IL28B SNP distribution. Similar IL28B SNPs allele frequencies were recorded for patients and controls. IL28B major allele homozygosis (for both SNPs tested) was tightly correlated with virological and clinical response (P = 0.002). A statistically significant association was limited to 'difficult‐to‐treat' (G1/4) HCV genotypes. The IL28B genotype was a strong independent predictor of response (P = 0.007, OR 6.06; CI 1.65–22.22). The IL28B genotype was confirmed to be a useful predictor of response to IFN‐based therapy in patients with HCV and MC. The very close correlation between IL28B SNP distribution, virological and clinical response definitively confirmed the key role played by HCV in MC. Conversely, the IL28B genotype does not seem to influence the evolution to MC.